Antimicrobial Active Polymers in Food Packaging - Guarda-Moraga, A; Galotto-Lopez, M; Lopez de Dicastillo-Bergamo, A (wiley, 2015)
In the last decades there has been a paradigm shift in food packaging. Nowadays it is not only expected that food packaging act as a protective food barrier; what is expected is that during the period of time that the package is in direct contact with food, it will have a positive effect over food quality, safety and shelf life, becoming "active packaging." Within the different active packaging systems, antimicrobial packaging has become the focus of great attention as it acts on the food surface where the microorganisms grow. In this chapter, a review of the different antimicrobial agents that are included in polymer matrix is presented, including the different mechanisms to include these antimicrobial agents in the polymer and their kinetic release. © 2015 Scrivener Publishing LLC. All rights reserved.